ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHATANI SORGUM DI KABUPATEN GUNUNGKIDUL - Retno Wiji Gupito; Irham Irham; Lestari Rahayu Waluyati (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2014)
The objective of this study are : (1) to understand about the contribution of sorghum farming income to total household income, (2) factors that influence sorghum farming income, and (3) income distribution level of sorghum farmers in Gunungkidul Regency.The basic methodused in this studyis descriptive-analytic. Sampling method used in this study is purposive sampling. The data weretaken from 30 farmers in study area. The data was collected by an interview,questionnaires and literatures study case.In order to learn the several factors influencing income level, isused multiple linear regression method.On the other hand,the level of total income distribution of sorghum farmerswas analylizedby using Gini Ratio and Lorenz Curve. The results of this study showsthat shorgum farming incomecontributes 2% for total farmers income. This study also show that sorghum farming does not cause inequality income in the study area. Several factorsthat affect sorghum farmers income positively are the land size and seed prices.